Accuracy of the medication list in the electronic health record—implications for care, research, and improvement. (15th May 2018) - Walsh, Kathleen E; Marsolo, Keith A; Davis, Cori; Todd, Theresa; Martineau, Bernadette; Arbaugh, Carlie; Verly, Frederique; Samson, Charles; Margolis, Peter
Abstract: Objective: Electronic medication lists may be useful in clinical decision support and research, but their accuracy is not well described. Our aim was to assess the completeness of the medication list compared to the clinical narrative in the electronic health record. Methods: We reviewed charts of 30 patients with inflammatory bowel disease (IBD) from each of 6 gastroenterology centers. Centers compared IBD medications from the medication list to the clinical narrative. Results: We reviewed 379 IBD medications among 180 patients. There was variation by center, from 90% patients with complete agreement between the medication list and clinical narrative to 50% agreement. Conclusions: There was a range in the accuracy of the medication list compared to the clinical narrative. This information may be helpful for sites seeking to improve data quality and those seeking to use medication list data for research or clinical decision support.